Comparison of the Quality of Life of Cancer Patients with Pain Treated with Oral Controlled-Release Morphine and Oxycodone and Transdermal Buprenorphine and Fentanyl - Leppert, Wojciech; Nosek, Krzysztof (Current Pharmaceutical Design, 2019)
Aim: To compare the effects of oral morphine and oxycodone and transdermal fentanyl and buprenorphine on quality of life (QoL) of cancer patients with severe pain. Patients and Methods: Cancer patients with severe pain (NRS 6-10) treated at home and in outpatient clinics who failed to respond to non-opioids and/or “weak” opioids were randomized to morphine, oxycodone, fentanyl, or buprenorphine treatment for 28 days. Immediate-release oral morphine was rescued analgesic and 10-ml lactulose twice daily was prophylaxis of constipation; no antiemetics were used for prophylaxis. Results: Above all, 62 patients participated and 53 patients completed the study. Good analgesia was obtained with all 4 opioids. Morphine was associated with the less negative impact of pain on the ability to walk and normal work, and tendency on activity (BPI-SF) and lower consumption of rescue morphine. All 4 opioids elicited similar adverse effects. According to ESAS, the intensity of nausea and drowsiness increased at the beginning but decreased as treatment continued. Appetite, well–being, anxiety, depression, and fatigue improved. No changes were seen in constipation, vomiting and dyspnea. Constipation was rarely observed with all opioids (BFI). Any opioids improved overall QoL and emotional functioning with tendency improving physical functioning (EORTC QLQ-C15-PAL). Activity improved (Karnofsky). Morphine induced greater improvement in physical functioning and trend in improvement mood (HADS). Conclusion: All opioids significantly improved patients’ QoL. Morphine induced less negative impact of pain on daily activities and greater improvement in physical functioning with trends of better mood and less intense fatigue.
Keywords: cancer